Real-World Data on Adult T-Cell Leukemia/Lymphoma in Latin America: A Study From the Grupo de Estudio Latinoamericano de Linfoproliferativos. (2021) - Malpica, Luis; Enriquez, Daniel J.; Castro, Denisse A.; Peña, Camila; Idrobo, Henry; Fiad, Lorena; Prates, Maria; Otero, Victoria; Biglione, Mirna; Altamirano, Milagros; Sandival-Ampuero, Gustavo; Aviles-Perez, Ursula; et al.
Abstract : PURPOSE: Adult T-cell leukemia/lymphoma (ATLL) is an aggressive disease caused by the human T-cell leukemia virus type 1. Real-world data of ATLL in Latin America are lacking. PATIENTS AND METHODS: We analyzed patients with ATLL (acute, lymphomatous, chronic, and smoldering) encountered in 11 Latin American countries between 1995 and 2019. Treatment response was assessed according to the 2009 consensus report. Survival curves were estimated using the Kaplan-Meier method and log-rank test. RESULTS: We identified 253 patients; 226 (lymphomatous: n = 122, acute: n = 73, chronic: n = 26, and smoldering: n = 5) had sufficient data for analysis (median age 57 years). Most patients with ATLL were from Peru (63%), Chile (17%), Argentina (8%), and Colombia (7%). Hypercalcemia was positively associated with acute type (57% v lymphomatous 27%, P = .014). The median survival times (months) were 4.3, 7.9, 21.1, and not reached for acute, lymphomatous, chronic, and smoldering forms, with 4-year survival rates of 8%, 22%, 40%, and 80%, respectively. First-line zidovudine (AZT)-interferon alfa (IFN) resulted in an overall response rate of 63% (complete response [CR] 24%) for acute. First-line chemotherapy yielded an overall response rate of 41% (CR 29%) for lymphomatous. CR rate was 42% for etoposide, cyclophosphamide, vincristine, doxorubicin, and prednisone versus 12% for cyclophosphamide, vincristine, doxorubicin, and prednisone–like regimen ( P < .001). Progression-free survival at 1 year for acute type patients treated with AZT-IFN was 67%, whereas 2-year progression-free survival in lymphomatous type patients who achieved CR after chemotherapy was 77%. CONCLUSION: This study confirms Latin American ATLL presents at a younger age and has a high incidence of lymphomatous type, low incidence of indolent subtypes, and worse survival rates as compared with Japanese patients. In aggressive ATLL, chemotherapy remains the preferred choice for lymphomatous favoring etoposide-based regimen (etoposide, cyclophosphamide, vincristine, doxorubicin, and prednisone), whereas AZT-IFN remains a good first-line option for acute subtype.